The rise of temporary employment in Japan: Legalisation and expansion of a non-regular employment form - Jun Imai (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2004)
This discussion paper examines the institutionalization process of a non-regular employment form especially focusing on the establishment of the temporary dispatching work (haken) system. The institutionalization process of the haken system can be divided into three periods: delegalisation (1947-86), legalisation (1986-99), and diffusion (1999-). Declining labor strength, the emergence of deregulation bodies, and the changing attitude of the Ministry of Labor (MHLW) characterize the legal developments. Together with the liberalization of private job placement and the expansion of fixed-term contract work, temporary work became an important sources of flexible and skilled labor, and expanded more rapidly than other employment forms in the late 90s. In this development, temporary help firms started to reframe their business as 'personnel services,' and have positioned themselves to replace the traditional firm-internal supply of mobile employees such as shukkô and tenseki with external dispatched employees of temporary help firms.
Keywords: 330; Japan; temporary work; non-regular employment; labor market; (de-)regulation; Befristeter Arbeitsvertrag; Ungeschützte Beschäftigung; Japan